Democratizing Molecular Diagnostics for the Developing World. Issue 1 (1st January 2014) - Abou Tayoun, Ahmad N.; Burchard, Paul R.; Malik, Imran; Scherer, Axel; Tsongalis, Gregory J.
Abstract: Objectives: Infectious diseases that are largely treatable continue to pose a tremendous burden on the developing world despite the availability of highly potent drugs. The high mortality and morbidity rates of these diseases are largely due to a lack of affordable diagnostics that are accessible to resource-limited areas and that can deliver high-quality results. In fact, modified molecular diagnostics for infectious diseases were rated as the top biotechnology to improve health in developing countries. Methods: In this review, we describe the characteristics of accessible molecular diagnostic tools and discuss the challenges associated with implementing such tools at low infrastructure sites. Results: We highlight our experience as part of the "Grand Challenge" project supported by the Gates Foundation for addressing global health inequities and describe issues and solutions associated with developing adequate technologies or molecular assays needed for broad access in the developing world. Conclusions: We believe that sharing this knowledge will facilitate the development of new molecular technologies that are extremely valuable for improving global health.